A Perceptual Study on Financial Services Innovation - Gupta, Shaveta; Dogra, Bairam; Vashisht, A. K. (Gyan Management Journal, 2011)
The financial services industry has undergone a dramatic transformation in recent decades necessitating new ideas that is where financial innovation comes into being. Financial innovation is the act of creating and then popularizing new financial instruments, financial technologies, institutions and markets. The financial services sector is awash in opportunities. Financial markets are always innovating. Realizing the importance of financial innovations in the financial services industry, the current study has covered the financial institutions’ outlook towards innovation in financial services industry.